Environmental Degradation and Development Diplomacy for Nepal - Basnyat, Niranjan Man Singh (NCWA Annual Journal, 2023)
This article aims to shed light on the challenges of global warming and climate change. The disasters produced by such phenomena are impacting the lives of people inhabiting the mountains, hills, and Tarai areas of Nepal. It also explains how to safeguard our ecological environment and mitigate the effects of global warming and climate change. Similarly, it also elaborates on how Nepal can face this difficulty as 80 percent of our population has been affected and the income of the people has been diminishing with low productivity in agriculture. With the active pursuance of development diplomacy under the overall economic diplomacy as a Middle Income Country (MIC), it is envisaged that Nepal will be able to cope with the new situation at the time of world recession as well as facing the adverse aftermath of Covid-19 pandemic with the good preparation to negotiate and implement the projects.